Trajectories of common people: Everyday life in Mallet-PR (1912-1940) - Kosinski, Lucas; Sochodolak, Hélio [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2019)
Criminal records associated with other sources such as executive and legislative documents and newspaper articles reveal suggestive possibilities for writing about the history of everyday practices. We took as our focus the criminal cases of homicides and personal injuries registered in the municipality of Mallet that had their origins in the territorial occupation of southern Paraná. We selected sources from the founding of the municipality in 1912 to 1940, which coincides with a relative increase in criminal records. Our objective here is to approach the daily life of residents of Mallet in light of Michel de Certeau's theoretical considerations, specifically the notions of strategies, tactics, spaces, places and trajectories.
Trajetórias de pessoas sem fama: Vida cotidiana em Mallet-PR (1912-1940)
Keywords: Daily life; Judicial cases; Regional history